The Understanding of Pre-Service Physics Teachers on Electric Circuit Concept - Anita Anita; Sy. Lukman Hakim Assagaf; Boisandi Boisandi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
The purpose of this research was to find out the descriptive of pre-service physics teachers understanding of the concept of electrical circuits, especially in the characteristic of series circuits and parallel circuits. The method used in this research was a descriptive method. The sample of this research was the fourth-grade students who took Basic Electronics course. The primary data of this research collected from the students’ test consisted of 12 multiple choices. Data analysis concluded that the student’s understanding of the concept of the electric circuit was low, with an average percentage of total indicators of 84.4%.